BENTUK PENYAJIAN TARI JEPIN SELENDANG DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA - Andina Silvana; Ismunandar Ismunandar; Regaria Tindarika (Universitas Tanjungpura, 2020)
AbstractThis research was motivated by the researcher's desire to examine the The Performance Form of Tari Jepin Selendang on Kelurahan Siantan Hilir Kecamatan Pontianak Utara and to document a complete data and information of Tari Jepin Selendang in the form of writing as well as pictures and videos, This study used a descriptive method in a qualitative form and uses a choreographic approach. Based on the results of research, The Performance Form of Tari Jepin Selendang, the dance movement consisted of a variety of opening movements, namely jepin empat-empat steps, the variety of content movements, namely gerak anyam masuk, gerak raddat and gerak buka anyam and the variety of closing movements was the jepin empat-empat. The floor designs were straight and curved. The musical instruments used were Accordions, Beruas, Tambourines, Gambus, Violins and Tawak. The group designs are unison, alternate and canon groups. Makeup used realistic makeup and the clothes used are baju kurung, Malay patterned fabric, lotus and the accessories used were lipat pandan bun, kembang goyang and earrings. The property was a colorful shawl. The theme is non-literary. Multiple cone dramatic design and the dynamics of motion, tempo and level. Keywords: Performance Form, Tari Jepin Selendang